1994
DOI: 10.1159/000117033
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Neuropathy with Liability to Pressure Palsies Masquerading as Slowly Progressive Polyneuropathy

Abstract: Hereditary neuropathy with liability to pressure palsies (HNLPP) is a peripheral nerve disorder in which recurrent pressure palsies are associated with pathological swelling (‘tomacula’) of myelinated nerve internodes. We report a patient with a slowly progressive polyneuropathy associated with substantial slowing of conduction velocities initially suggestive of an acquired or hereditary demyelinating polyneuropathy. However, repeat electrodiagnostic studies demonstrated that conduction slowing and partial con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 10 publications
0
7
0
3
Order By: Relevance
“…11 This autosomal dominant disorder, mostly associated with a 17p11.2 deletion including the PMP-22 gene, 2 may have atypical phenotypes. 3,8,9 We report here the first case of molecular genetically confirmed HNPP manifested by a recurrent polyradiculoneuropathy.…”
Section: Accepted 1 March 1997mentioning
confidence: 81%
See 1 more Smart Citation
“…11 This autosomal dominant disorder, mostly associated with a 17p11.2 deletion including the PMP-22 gene, 2 may have atypical phenotypes. 3,8,9 We report here the first case of molecular genetically confirmed HNPP manifested by a recurrent polyradiculoneuropathy.…”
Section: Accepted 1 March 1997mentioning
confidence: 81%
“…4 The prevalence of the 17p11.2 deletion was 68% in the series of HNPP patients reported by Mariman et al 10 and 90% in our own series, 7 diagnosed in accordance with the electrophysiological criteria described by Gouider et al 4 Sporadic cases with the 17p11.2 deletion have also been reported. 2 Clinically atypical forms of HNPP, namely sensorimotor polyradiculoneuropathies with a chronic progressive course, have recently been described: two reports based on biopsy data 3,8 and one on a genetic study. 1,9 However, only 1 case of acute and recurrent polyneuropathy has previously been reported 6 : focal tomaculous thickenings were observed, but deletion studies could not be carried out at that time.…”
Section: Short Reportsmentioning
confidence: 99%
“…These include increased distal motor latencies, mildly decreased nerve conduction velocities, and multiple superimposed mononeuropathies including a focal conduction block at a site of common compression (peroneal neuropathy at the fibular head). 4,11 The fulminant nature of this case underscores its inclusion into the differential diagnosis of subacute polyneuropathies. Indeed, most cases of HNPP are documented as single-nerve palsies appearing sequentially in a more chronic setting.…”
Section: Discussionmentioning
confidence: 84%
“…There are rare instances of HNPP presenting as a distal polyneuropathy with a duration in the order of years. 4,10,15,16 The more typical pattern is that of single-nerve involvement resolving in days to months and then followed by a motor deficit in the same or in another distribution. Of the 69 acute nerve palsies that Gouider et al 6 studied in 13 families with documented HNPP, only 4 cases were found that occurred simultaneously in different limbs.…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of cases patients recover from palsies completely, however, repeated attacks can prevent full reversal, and with aging, patients frequently develop a largely symmetric polyneuropathy that mimics CMT1. This can easily lead to the establishment of wrong diagnosis (Felice et al 1994). Additional presenting phenotypes are acute brachial paralysis, confluent mononeuropathy multiplex and the disputed category of oligosymptomatic patients (Pareyson et al 1996;Kumar et al 1999).…”
Section: Introductionmentioning
confidence: 99%